2016
DOI: 10.1007/s10329-016-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral responses to routine procedures in captive common marmosets (Callithrix jacchus)

Abstract: The effect of routine captive procedures on the welfare of species used as experimental models in biomedical research is of great interest, since stress may alter the generalization and interpretation of results. This study investigated behavioral and endocrine (fecal cortisol) reactivity patterns in common marmoset (Callithrix jacchus) adult males (N = 10) and females (N = 9) subjected to three types of routine procedures in captivity: (1) moving to a same-sized cage (P1), to a smaller cage (P2), and (2) firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…However, no report analyzes all parameters and compares all variables we included and used a large sample size while making use of the appropriate statistical methods. It is important to consider calculating reference values for each individual facility, using their own animals, diet, sedation protocols, catching methods, etc., as these values can influence laboratory parameters [ 12 , 13 , 16 , 17 , 18 ]. However, in this dataset it was attempted to exclude and investigate the effect of as many variables as possible to achieve a representative and statistically correct collection of reference intervals to be used at facilities that do not have the means to calculate them themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, no report analyzes all parameters and compares all variables we included and used a large sample size while making use of the appropriate statistical methods. It is important to consider calculating reference values for each individual facility, using their own animals, diet, sedation protocols, catching methods, etc., as these values can influence laboratory parameters [ 12 , 13 , 16 , 17 , 18 ]. However, in this dataset it was attempted to exclude and investigate the effect of as many variables as possible to achieve a representative and statistically correct collection of reference intervals to be used at facilities that do not have the means to calculate them themselves.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that this heightened activation of the cortisol pathway was associated with sex-specific reactions to the stress of the move, it is much more likely to reflect sex-specific metabolic differences in a catabolic hormone. Female marmosets have been found to have significantly higher baseline salivary cortisol concentrations than males (Ash, Smith, Knight, & Buchanan-Smith, 2018), and they are known to significantly differ in their response to acute stressors such as the presence of intruders (Ross & French, 2011), and reactions to social challenge (de Menezes Galvao, Ferreira, de Sousa, & Galvao-Coelho, 2016). In addition, previous work on other marmoset colonies has suggested that males are longer lived than females both in median and maximum lifespan (Nishijima et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As causas que podem levar o paciente a evoluir para um quadro de PCR são variadas, podendo ser desde um choque circulatório ou, até mesmo, uma doença cardiovascular. Contudo, estar em um ambiente hospitalar ajuda, de certa forma, a equipe de enfermagem quando se trata de dar celeridade à assistência prestada devido ao monitoramento do paciente sobre os cuidados da equipe (MENEZES;SOUZA, 2015).…”
Section: )unclassified